Long-term mobility of the esophagus in patients undergoing catheter ablation of atrial fibrillation: data from computer tomography and 3D rotational angiography of the left atrium - Stárek, Zdeněk; Lehar, František; Jež, Jiří; Žbánková, Alena; Kulík, Tomáš; Wolf, Jiří; Novák, Miroslav (Journal of interventional cardiac electrophysiology, 2016)
PURPOSE: Computed tomography (CT) and 3D rotational angiography (3DRA) of the left atrium (LA) are used to evaluate the esophagus prior to radiofrequency ablation for atrial fibrillation. The aim of this study was to compare preprocedural and periprocedural views of the esophagus and the left atrium. METHODS: From September 2011 to August 2012, 3DRA and CT of the LA were performed on 56 patients before they underwent catheter ablation of atrial fibrillation. The 3DRA was performed periprocedurally, and the CT was performed an average of 20 days prior to the procedure. 3D models of the LA and the esophagus were then segmented on the EP Navigator V 3.1 workstation. Five positions of the esophagus, A-E, in order from left to right, were evaluated. RESULTS: The most common position of the esophagus was behind the left part of the LA (CT, position B (n = 26)) and behind the central part of the LA (3DRA, position C (n = 21)). The maximum shift of the esophagus was three positions, and the average shift was 0.857 ± 0.766 of a position. There was a shift of one position in 44.6 % of the patients, two positions in 17.9 %, and three positions in 1.8 %. A statistically significant difference was found between the positions of the esophagus when the 3DRA and CT evaluations were compared. CONCLUSIONS: The most common position of the esophagus was behind the middle and left part of the LA. The outpatient views of the esophagus obtained before ablation did not reflect the position of the esophagus at the beginning of the procedure.
Keywords: Surgery, Computer-Assisted; rotace; Female; Atrial Fibrillation; zobrazování trojrozměrné; Imaging, Three-Dimensional; Catheter ablation of arrhythmias; výsledek terapie; ženské pohlaví; Computed Tomography Angiography; srdeční síně; longitudinální studie; Catheter Ablation; Reproducibility of Results; Computer tomography of the heart; pohyb těles; lidé; Postoperative Care; 3D rotational angiography of the left atrium; Sensitivity and Specificity; Atrioesophageal fistula; Esophagus imaging; katetrizační ablace; Treatment Outcome; senzitivita a specificita; koronární angiografie; pooperační péče; Motion; Humans; retrospektivní studie; reprodukovatelnost výsledků; Esophagus; Male; předoperační péče; Heart Atria; Preoperative Care; fibrilace síní; ezofágus; lidé středního věku; mužské pohlaví; Rotation; CT angiografie; chirurgie s pomocí počítače; Retrospective Studies; Middle Aged; Longitudinal Studies; Atrial fibrillation; Coronary Angiography